Vitamin D insufficiency and sleep disturbances in children with ADHD: a case-control study - Zhang, Panpan; Liu, Yang; Ma, Yan; Zhao, Tingting; Zhang, Chan; Sun, Hao (Frontiers in Psychiatry, 2025)
IntroductionAttention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorders often co-occurring with sleep problems and other physical disorders. Vitamin D regulates sleep and supports normal brain function. Regrettably, no studies have looked at whether vitamin D insufficiency exacerbates sleep problems in ADHD children and further affects ADHD symptoms.ObjectiveThis study aimed to examine whether vitamin D insufficiency exacerbates sleep problems and ADHD symptoms in children aged 6–14 years.MethodsThis is a case-control study, 260 ADHD children (aged 6-14 years) were enrolled in, of whom 95 had vitamin D insufficiency and 165 had sufficiency. Collected all ADHD symptom severity and functional impairment scales, including Swanson, Nolan and Pelham (SNAP) scale, Integrated Visual and Auditory Continuous Performance Test (IVA-CPT), Conners parents symptom questionnaire (PSQ) and Weiss Functional Impairment Rating Scale-Parent Form (WFIRS-P). All guardians of children with ADHD complete the Children’s Sleep Habits Questionnaire (CSHQ).ResultsThe CSHQ total scores of the ADHD children in both groups were significantly higher than 41, which means that ADHD children overall have sleep problems. Compared to ADHD children with vitamin D sufficiency group, we observed significantly higher sleep duration and sleep disordered breathing scores in ADHD children with vitamin D insufficiency group (all p< 0.05). However, there was no direct effect of vitamin D insufficiency on the type of ADHD, symptoms or functional impairment (all p> 0.05). Further analyses showed a correlation between the CSHQ and symptoms, functional impairment scores in children with ADHD.ConclusionSleep problems are highly prevalent in children with ADHD. Vitamin D insufficiency has a significant impact on both sleep duration and sleep disordered breathing, but no notable direct effects on ADHD symptoms or functional impairment. Our findings underscore the importance of screening for vitamin D insufficiency in children with ADHD, particularly given its association with sleep disturbances, which may indirectly affect symptom severity.